SIKAP DAN PERILAKU KUSIR CIDOMO DI GILI TRAWANGAN - Syech Idrus; I Putu Gede; Lia Rosida; Lalu Masyhudi (Faculty of Social and Political Science, 2019)
The majority of Cidomo coachmen in Gili Trawangan graduated from elementary school, and has adequate expertise on controlling horses, as on average they earned the profession as a coachman for more than 10 years in the markets, terminals in the area of Pamenang, Gondang and Tanjung, North Lombok Regency. As they have the background of being a coachman in the markets and terminals without paying attention to the courtesy and hospitality, the technical guidance activities for the coachmen were carried out on the courtesy and hospitality of serving the tourists as the passengers. The result of the technical guidance activities shows that after the evaluation implementation, most of Cidomo coachmen have been able to practice the knowledge and skills obtained from the technical guidance activities in their work. However, there still some Cidomo coachmen are negligent or not used to saying greetings, hello and thank you. The main constraint faced in the implementation of this technical guidance is in terms of setting up the time and schedule of the activities, because not all Cidomo coachmen have the same time to attend the implementation of the activities.